Peranan Dukungan Pemerintah Terhadap Small and Medium Sized Enterprises di Bidang Pariwwisata Studi Kasus : Usaha Homestay di Bali (Indonesia) dan Phuket (Thailand) - , INDAH DEWI UTAMI, Drs. usmar Salam, MIS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tourism has become a part of peopleâs lives in Bali and Phuket major contributing role in development. Development of tourism in Bali and Phuket has progressed very rapidly in terms of both quality and quantity.It can be seen from the growing and increasing tourism infrastructure such as accommodation, transportation, recreation and entertainment facilities, communications, and tourist attractions. Homestay accommodation is one that is getting moldy in the community especially for small medium sized enterprises. Homestay concept that was once merely provide a place for guests to stay regardless of the rental price, has turned into a more modern homestay leads to pure business (money oriented). This thesis will focus on the governmentâs role in supporting in tourism sector, which will also affect the small and medium sized entreprises (SMEs), especially to entrepreneurs homestay.